Social Media and CSR - A Double-Edged Sword? - Caun, Stephanie. E. (2010)
The emergence of social media has given people the ability to instantaneously communicate with thousands of people through an online platform. In a very short period of time, this new form of media has managed to creep into the business domain and has provided very real opportunities for CSR to develop. As a result of being such a new phenomenon, the academic literature surrounding social media is scarce. Therefore this study intends to give an extensive and balanced insight into the positive and negative implications of social media on both businesses and stakeholders.